Physico-chemical Significance of Dye-Indicator Method in Complex Ions Variations in Aqueous Methanol System Mercuric Halide-Alkali Halide - Farasram, Rakesh; Farasram, P.L.; Desai, C.M. (Asian Journal of Chemistry, 2010)
The mercuric halide-alkali halide system was studied in aqueousphase spectrophotometric ally and it was found that six types ofcomplexes were formed. The aqueous phase of the system wasreplaced by aqueous methanol and it was found that as the methanolconcentration was increased in the system, the dielectric constantdecreased and complex formation susceptibility decreased.